Jus Tomat & Apel Dapat Menurunkan Kadar Kolesterol Terhadap Lansia: Tomato & Apple Juice Can Lower Cholesterol Levels in the Elderly - Donna Kusuma Wawarni; Saiful Gunardi; Jumari (Dohara POAJ, 2021)
Introduction: Therapy for cholesterol has not non-pharmacological treatment that is expected to be able to complete pharmacological treatment in lowering cholesterol levels by using tomato juice & apple. Methods: Design this research is Pre-Experimental Design with the form of One Group Pretest- Postest Design. Sampling techniques using purpose sampling with the number of respondents as many as 20 respondents, Analysis using Paired Sample T-Test statistics. Results: Design this research is Pre-Experimental Design with the form of One Group Pretest-postest Design. Sampling techniques using purpose sampling with the number of respondents as many as 20 respondents. Discussion: There was an effect of giving tomato and apple juice to the decrease in cholesterol levels in the elderly in the area RW 09 Grogol.